Accelerating amorphous polymer electrolyte screening by learning to reduce errors in molecular dynamics simulated properties - Tian Xie; Arthur France-Lanord; Yanming Wang; Jeffrey Lopez; Michael A. Stolberg; Megan Hill; Graham Michael Leverick; Rafael Gomez-Bombarelli; Jeremiah A. Johnson; Yang Shao-Horn; Jeffrey C. Grossman (Nature Communications, 2022)
Screening polymer electrolytes for batteries is extremely expensive due to the complex structures and slow dynamics. Here the authors develop a machine learning scheme to accelerate the screening and explore a space much larger than past studies.